2008
DOI: 10.1029/2007jb005234
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the effect of off‐fault damage on the velocity of a slip pulse

Abstract: [1] The effect of off-fault damage on the speed of ruptures propagating on faults in photoelastic Homalite plates was measured using high-speed digital photography. The offfault damage was composed of a network of fractures introduced by thermally shocking the Homalite in liquid nitrogen. The mode II rupture speed measured in damaged Homalite was significantly lower than the limiting Rayleigh speed of v r = 0.92 v s , even after the shear wave speed v s was reduced to a value appropriate for the fracture-damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…By reducing the shear-wave speed c S , the effect on rupture velocity is to lower the limiting Rayleigh speed, which is 0.92 c S for Mode II ruptures. However, BIEGEL et al (2008) found that damage reduced the rupture velocity below that expected, based solely on the lower shear-wave speed. They ascribed this additional reduction to a further dynamic reduction in modulus and to anelastic losses associated with frictional slip on the myriad of small off-fault fractures that comprise the damage.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…By reducing the shear-wave speed c S , the effect on rupture velocity is to lower the limiting Rayleigh speed, which is 0.92 c S for Mode II ruptures. However, BIEGEL et al (2008) found that damage reduced the rupture velocity below that expected, based solely on the lower shear-wave speed. They ascribed this additional reduction to a further dynamic reduction in modulus and to anelastic losses associated with frictional slip on the myriad of small off-fault fractures that comprise the damage.…”
Section: Introductionmentioning
confidence: 88%
“…Note that propagation is symmetric and both rupture tips accelerate to the limiting (Rayleigh) rupture velocity c R = 0.92c S for mode II propagation and then transition to supershear velocities approaching the P-wave speed (note, c P /c S = 2.1 for Homalite). BIEGEL et al (2008) introduced fracture damage into Homalite plates by using a razor knife to score a mesh of scratches on both sides of the plate spaced about 2 mm apart and oriented at ?/-45°to the loading axis, followed by immersion in liquid nitrogen for 45 seconds. The thermal shock produced a network of fractures with a mean spacing of about 1 cm as shown in Figure 5.…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…66AI7olrze Figure 3 shows a damaged sample from the study by Biegel et al (2008), in which we demonstrated that off-fault damage significantly reduces the rupture speed. The fracture damage was produced by scoring a grid onto both sides of the homalite sample with a razor knife and then dipping the sample into liquid nitrogen.…”
Section: Fiur 2 Eprienalcnfguatonsownguniffa Lodn Frm2nulaincrutmentioning
confidence: 99%